Combination of Anti-EGFR and Anti-VEGF Drugs for the Treatment of Previously Treated Metastatic Colorectal Cancer: A Case Report and Literature Review - Li, Yong; Chen, Xian; Li, Wenzhu; Ye, Yongsong; Du, Xiaohua; Sun, Shaodan; Liu, Lirong; Zhang, Haibo (Frontiers in Oncology, 2021)
The standard third-line treatment of metastatic colorectal cancer (mCRC) includes the small-molecule anti-vascular drugs（Regofenib and Fruquintinib）and the chemotherapy drug trifluridine and tipiracil hydrochloride（TAS-102）. There is no standard treatment for mCRC if the third-line treatment failed. Therefore, it is a pressing need to develop new therapeutic approaches to improve the survival of patients who developed drug resistance to the third-line treatment. In this study, we report a case of mCRC with RAS/BRAF wild-type, who was successfully treated using cetuximab in combination with fruquintinib after resistance to chemotherapy, bevacizumab, cetuximab and regorafenib. This patient responded to this combination regimen. Then, we discuss the mechanisms of action of this combination. Furthermore, we introduce the clinical trials on the combination regimens of anti-EGFR with anti-vascular monoclonal antibodies. Finally, we discuss the clinical explorations of using combination of anti-EGFR with small-molecule anti-VEGF drugs and their potential benefits. The clinical effects of small-molecule anti-vascular drugs in combination with anti-EGFR in the treatment of CRC warrant further explored